Cocoa powder triggers neuroprotective and preventive effects in a human Alzheimer's disease model by modulating BDNF signaling pathway. Issue 10 (16th August 2013) - Cimini, Annamaria; Gentile, Roberta; D'Angelo, Barbara; Benedetti, Elisabetta; Cristiano, Loredana; Avantaggiati, Maria Laura; Giordano, Antonio; Ferri, Claudio; Desideri, Giovambattista
Abstract The molecular mechanisms linking Aβ to the onset of neurotoxicity are still largely unknown, but several lines of evidence point to reactive oxygen species, which are produced even under the effect of nanomolar concentrations of soluble Aβ‐oligomers. The consequent oxidative stress is considered as the mediator of a cascade of degenerative events in many neurological disorders. Epidemiological studies indicate that dietary habits and antioxidants from diet can influence the incidence of neurodegenerative disorders such as Alzheimer's and Parkinson's diseases. In the recent years, a number of reviews have reported on neuroprotective effects of polyphenols in cell and animal models. However, the majority of these studies have focused only on the anti‐oxidant properties of these compounds and less on the mechanism/s of action at cellular level. In this work we investigated the effect of cocoa polyphenolic extract on a human AD in vitro model. The results obtained, other than confirming the anti‐oxidant properties of cocoa, demonstrate that cocoa polyphenols triggers neuroprotection by activating BDNF survival pathway, both on Aβ plaque treated cells and on Aβ oligomers treated cells, resulting in the counteraction of neurite dystrophy. On the light of the results obtained the use of cocoa powder as preventive agent for neurodegeneration is further supported. J. Cell. Biochem. 114: 2209–2220, 2013. © 2013 Wiley Periodicals, Inc.